2009
DOI: 10.1111/j.1502-3885.2009.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Weichselian glacial stage in Murchisonfjorden, Nordaustlandet, Svalbard

Abstract: Compared to the other islands in the Svalbard archipelago, Nordaustlandet offers only limited stratigraphical or sedimentological information on its Quaternary deposits. This article aims to fill the gap by presenting new results from glacial geological, sedimentological and chronological studies in the southern Murchisonfjorden area. Field data include reconnaissance mapping and detailed logging of vertical sections along cliff-face outcrops a few metres high adjacent to the present-day shoreline. Combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 47 publications
7
49
0
Order By: Relevance
“…This age matches well with the early part of the Kapp Ekholm interstadial (Formation F at Kapp Ekholm; Mangerud and Svendsen [8]) as dated by Eccleshall et al ([15]; ca 80 ka), as well as with the Early Weichselian interstadial recognised in Nordaustlandet (80-76 ka, unit 1 at Isvika; Kaakinen et al [16]) (Fig. 20).…”
Section: Event K-ii (Units 3-5 Ca 130 Ka)supporting
confidence: 61%
See 3 more Smart Citations
“…This age matches well with the early part of the Kapp Ekholm interstadial (Formation F at Kapp Ekholm; Mangerud and Svendsen [8]) as dated by Eccleshall et al ([15]; ca 80 ka), as well as with the Early Weichselian interstadial recognised in Nordaustlandet (80-76 ka, unit 1 at Isvika; Kaakinen et al [16]) (Fig. 20).…”
Section: Event K-ii (Units 3-5 Ca 130 Ka)supporting
confidence: 61%
“…The only other site with raised marine sediments suggested to be of similar age is found at Isvika on Nordaustlandet (unit 6, 40-38 ka: Kaakinen et al [16]) (Fig. 20), although other sites have sediments dated to this time within uncertainties (e.g.…”
Section: Event K-ii (Units 3-5 Ca 130 Ka)mentioning
confidence: 99%
See 2 more Smart Citations
“…Solomon et al 2007;Kwok et al 2009;Polyak et al As one of the activities of the International Polar Year 2007Year -2009, an expedition was organised to the Murchisonfjorden area, Nordaustlandet (Pohjola et al 2011). Earlier studies by Kaakinen et al (2009) and Kubischta et al (2010) indicated that coastal sections in Isvika bay contain glacial and marine sediment sequences extend− ing back to the beginning of the Weichselian glacial stage. The marine sediments of the bay could complement the geological history of the area, as was recently shown in the foraminiferal study by Kubischta et al (2011).…”
Section: Introductionmentioning
confidence: 99%